New mode for the on-line determination of oxonium ion in different strong acids using CFIA via the use of homemade linear array Ayah 5Sx4-ST- 5D solar CFI analyser - M. A. Shakir, Issam; F. A. AL-Razack, Hussein (Iraqi Journal of Science, 2023)
New mode for the on-line determination of oxonium ion in different strong acids using CFIA via the use of homemade linear array Ayah 5Sx4-ST- 5D solar CFI analyser